Rate analysis of drawing solid model-based on orthogonal and isometric projection - Setiadi, Bayu Rahmat; Jarwopuspito; Sarwanto, Dwi (AIP conference proceedings, 2023)
The purpose of this study was to determine the difference in the speed of drawing solid modeling using working drawings based on orthogonal projections and isometric projections. This research is included in quantitative descriptive analysis. The research subjects were students of class XI Wonosari Vocational High School 2 who took Manufacturing Drawing Engineering for the academic year 2020/2021. The number of research subjects to be studied amounted to 17 students. Data were collected using the test method. Data analysis was performed using descriptive statistical analysis. The results show that the rate of drawing solid models based on isometric projections has an average time of 5.6 minutes faster than using orthogonal projections. Drawing solid models based on orthogonal projections have an average time of 29.6 minutes, with the fastest time being 15.4 minutes and the longest time being 45.9 minutes. At the same time, the speed of drawing solid models based on isometric projections has an average time of 24.0 minutes, with the fastest time of 14.0 minutes and the longest time of 36.0 minutes.